reduza os termos semelhantes de 3a-(b-a)+(5b-2a)
Soluções para a tarefa
Respondido por
34
3a - (b - a) + (5b - 2a)
3a - b + a + 5b - 2a
3a + a - 2a - b + 5b
2a + 4b
3a - b + a + 5b - 2a
3a + a - 2a - b + 5b
2a + 4b
daisycastro:
de nada, bons estudos!!!!
Respondido por
8
= 3a - (b - a) + (5b - 2a)
= 3a - b + a + 5b - 2a
= 3a + a - 2a - b + 5b
= 4a - 2a + 4b
= 2a + 4b
= 2(a + 2b)
= 3a - b + a + 5b - 2a
= 3a + a - 2a - b + 5b
= 4a - 2a + 4b
= 2a + 4b
= 2(a + 2b)
Perguntas interessantes
Informática,
9 meses atrás
Sociologia,
9 meses atrás
História,
1 ano atrás
Direito,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás